The Relationship between Serum Sclerostin Levels and Bone Mineral Disorders and Vascular Calcification in Hemodialysis Patients - Abdallah, Emad; Sherif, Nevine; Mosbah, Osama; Metwally, Amna; Abd ElAzim, Ibrahim; Mahmoud, Ola; Farouk, Mohamed; Mamdouh, Samah; El-Shishtawy, Samya; Mohamed, Asmaa (Open Access Macedonian Journal of Medical Sciences, 2021)
Background and aim of the study: Sclerostin is produced by osteocytes and has been shown to down-regulate the synthesis of many markers of bone formation by osteogenic cells. The aim of this study to investigate the relationship between serum sclerostin levels and bone mineral disorders and vascular calcification in hemodialysis patients (HD). Methods:This is a cross-sectional study of 70 patients with ESRD on regular HD for at least six months, Theodor Bilharz Research Institute, Giza, Egypt.Twenty-five subjects who matched the ages, genders, and demographics of the study patients were included as a control group.All patients and control groups included in the study underwent a full through history and clinical examination. Serum calcium, phosphorus, alkaline phosphatase and intact PTH (iPTH) levels were measured. Serum sclerostin was measured by an ELISA. Bone Mineral Densitometry Measurements BMD (g/cm2) was determined by dual-energy X-ray absorptiometry (DXA). CT scan was done to detect the presence or absence of vascular calcification and transthoracic echocardiogram to detect the presence or absence of valvular calcification. Results:The mean seumscleostin levels was a statistically significant high in the HD patients when compared with the control group (156.8 ±121.4 Vs.29.38±0.84, p =0.0001 ) and statistically significant high mean ALP in the HD patients when compared with the control group (147.2 ± 94.3 Vs. 38.8 ±23.4, p = 0.0001). The mean BMD was statistically significant low in the HD patients when compared with the controls (0.839±0.086 g/ m2 Vs.1.306 ±0.153 g/ m2, p = 0.0001).The mean seumscleostin levels was statistically significant high in the HD patients with vascular and valvular calcification when compared with HD patients without calcification.Using spearman correlation coefficient analysis, there was statistically significant negative correlations between serum sclerostin levels and iPTH(r=-0.362, p =0.0021), ALP (r=-0.301, p =0.0114), and BMD (r=-0.469, p =0.0278 ), and there was a statistically significant positive correlation between serum sclerostin levels and phosphate(r=0.5829, p =0.0001 ).Independent predictors of BMD in HD patients were determined using multi-variate regression analysis. Sclerostin levels, iPTH, ALP, and age were found to be independent predictors of BMD. Conclusion: High sclerostin levels in patients with ESRD on HD were associated with high risk of vascular and valvularcalcification and were independent predictors of low BMD in such population.